Pengaruh Disiplin Kerja dan Motivasi Kerja terhadap Kinerja Karyawan - Prasetiyani, Desi (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
This study aims to determine the effect of work discipline and work motivation on employee performance. The research method used is quantitative, with a total population and sample of 80 respondents. Data analysis includes validity and reliability tests, classical assumption tests, regression analysis, correlation analysis, determination analysis, and hypothesis testing. The results of this study indicate a strong correlation between work discipline and work motivation in influencing employee performance. The multiple linear regression equation shows that an increase in work discipline positively impacts employee performance, as does an increase in work motivation. The coefficient of determination suggests that work discipline and work motivation contribute significantly to improving employee performance, while the remaining portion is influenced by other factors. Furthermore, hypothesis testing confirms that work discipline and work motivation simultaneously have a significant impact on employee performance. These findings provide valuable insights for organizations in formulating policies and strategies aimed at enhancing employee performance. Improving work discipline and motivation can be an effective approach to achieving better organizational outcomes.